(untitled) (Archives of Mechanics - Test, 2008)
The present investigation is a study of the effect of rotation on the characteristics of Rayleigh waves propagation in a homogeneous, isotropic, thermoelastic diffusive half-space in the framework of different theories of thermoelastic diffusion, including the Coriolis and Centrifugal forces. The medium is subjected to stress-free, thermally insulated/isothermal and chemical potential boundary conditions and is rotating about an axis perpendicular to its plane. Secular equations of surface wave propagation in the considered media are derived. The phase velocities and attenuation coefficients of surface wave propagation have been computed by using the irreducible case of Cardano’s method, with the help of DeMoivre’s theorem known from the secular equations. The amplitudes of surface displacements, temperature change, concentration and the specific loss of energy are computed numerically. Rotation effect on the phase velocity, attenuation coefficient, amplitudes of surface wave propagation and specific loss of energy are presented graphically in order to illustrate and compare the analytically obtained results. Some special cases of frequency equation are also deduced from the present investigation.